Analysis of the distribution of Astragalus membranaceus var. mongholicus in Inner Mongolia under climate change using the GEE platform - Jingxia Guo; Chunhong Zhang; Mingxu Zhang; Yaqiong Bi; Mengchao Wang; Minhui Li (Science of Traditional Chinese Medicine)
Abstract. Objective. Astragali Radix, commonly used in traditional Chinese medicine, is subjected to an analysis of the habitat distribution of Astragalus membranaceus var. mongholicus in the Inner Mongolia Autonomous Region of China under climate change. This analysis is crucial for the conservation of medicinal plants, the assessment of their adaptability to climate change, and the promotion of sustainable development in the ecological environment. Methods. This study explores the currently suitable habitats for A. membranaceus var. mongholicus using a random forest species distribution model on the Google earth engine platform. Based on future climate data, the study predicts distribution dynamics for 4 time periods (2021–2040, 2041–2060, 2061–2080, and 2081–2100) under three climate change scenarios (SSP126, SSP245, and SSP585). Results. The results indicate that under current climatic conditions, the suitable habitat distribution of A. membranaceus var. mongholicus is mainly concentrated in the southwestern region of Inner Mongolia. Under future climate change scenarios, there is a varying degree of contraction in suitable habitats, with notable reductions. Particularly, under the SSP126 scenario (2081–2100), there is a significant decrease of 22.77% in suitable habitat. The SSP245 scenario (2041–2060) exhibits the most pronounced habitat loss, with a reduction of 36.38%. Additionally, with climate change, the overall suitable range of A. membranaceus var. mongholicus is expected to shift toward higher latitudes and contract. Conclusion. This study can be used to improve conservation efforts for wild A. membranaceus var. mongholicus. It also provides a scientific basis for the cultivation of this medicinal plant in the context of climate change. This, in turn, can encourage more industries to achieve both sustainable development and economic benefits, providing valuable insights for building a low-carbon economy.